Effective Utilization of Private Pharmacies in Tuberculosis Care: A Potential Link in India - Janmejaya Samal, Dr (Asian Journal of Pharmaceutics (AJP), 2016)
Tuberculosis (TB) is a global public health crisis. Around 25% of TB cases are found in India. Research reveals that TB management by private sectors in India is erratic in nature and around 50-80% of TB patients visit private health facilities for seeking care. The private facilities include private hospitals, nursing homes, private practitioners - qualified and unqualified/individual and institutional, traditional healers, and the pharmacies. The private pharmacies usually function as anti-TB drug dispensing depots where patients, especially the chest symptomatics or the cough symptomatics, seek medical care and buy medicines over the counter hoping to get rid of their conditions. Several aspects of private practitioners have been studied that includes knowledge, attitude, practice, prescription behavior, etc. However, studies regarding the role of private pharmacies in TB care are very few. This article briefly examines the effective utilization of private pharmacies including the probable advantages of distributing free quality TB drugs at private pharmacies and the contribution of the same in controlling TB in India. This article draws experiences from different settings where similar attempts have been made and tries to examine the same in a pan India context